Electric Motors for Variable-Speed Drive of Lock Valves - Aleksey V. Udovichenko (MDPI AG, 2021)
Improving the operational reliability of nuclear power plants, combined heat and power plants (CHP), as well as oil and gas pipelines is a priority task in the development of a variable-speed drive for lock valves used at these facilities. This paper analyzes the technical requirements for such devices: the motor has been selected, its electrical equilibrium and moment equations have been obtained; recommendations for the selection of the kinematic drive scheme have been formulated. Based on the theoretical data obtained, a prototype has been developed, manufactured, and tested.